TEACHING A FOREIGN LANGUAGE TO STUDENTS OF HIGHER EDUCATION INSTITUTIONS THROUGH READING EXERCISES (ON THE EXAMPLE OF STUDENTS OF NON-PHILOLOGICAL SCIENCES) - Ra'no Ibrohimovna Oripova; Ma'rifjon Ma'mirdjanovich Axmedov; Nigora Maxmudovna Djampulatova; Madinaxon Fayzulloqizi Nuritdinova (The Bioscan, 2024)
This article studies the role and importance of reading exercises in the process of teaching a foreign language in higher education institutions. The article analyzes the methods of teaching a language, especially for students in non-philological education. Methodological approaches to language learning, the impact of reading exercises on increasing students' success in the language learning process are considered. Also, difficulties in learning a foreign language and effective methods to overcome them, including interactive and practical approaches, are analyzed. The role and methodological approaches of reading exercises in the process of teaching a foreign language to students in higher education institutions, especially in the field of music education, are studied. Methods and practical exercises adapted for students in the field of music education in teaching a foreign language are considered.